Wheat and chaff: The degree to which strategic management principles are integrated within corporate social responsibility reporting among large Canadian firms - Mark Fuller (International Journal of Corporate Social Responsibility (JCSR), 2022)
This empirical study examines the degree to which strategic principles are reflected in the corporate social responsibility (CSR) reporting practices among Canada's largest corporations. In a two-phased approach, three time periods of corporate disclosure from 2016 to 2020 were studied. Using an organizational flowchart derived from the literature, CSR disclosures were organized according to six degrees of strategic integration. Analysis reveals a bimodal distribution of firms, with one mode representing firms with a fully integrated reporting framework, and another mode representing firms with the partial integration of strategic management principles. Inconsistent patterns of progress in reporting practices were discovered, with some firms demonstrating improved reporting practices while others stagnated or declined. Overall, a generalized improvement in strategic integration during our multi-year examination was observed. While this work has implications for corporate social responsibility theory, recommendations for CSR practitioners are also discussed.
Keywords: 650; Canada; Corporate disclosures; Corporate social responsibility reporting; Strategic CSR; Strategic integration; Sustainability reports; Voluntary reporting